DAMPAK TERPAAN KONTEN MEDIA SOSIAL INSTAGRAM TERHADAP KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA SMK UNITOMO SURABAYA - Ishadi Fadillah, M Reza; Pasopati, Rommel Utungga; Andharu, Devito (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
This research investigates the link between exposure to social media content and the interpersonal communication skills of adolescents, focusing on students at SMK Unitomo Surabaya. Employing a quantitative correlational method, data were gathered via questionnaires administered to 139 purposively selected students. The instrument underwent validity and reliability testing, confirming that all items met the necessary standards. Findings from a simple linear regression analysis demonstrated a significant and positive association between social media exposure and interpersonal communication (r = 0.672, p < 0.01). The coefficient of determination (R² = 0.452) indicates that 45.2% of the variation in interpersonal communication skills can be attributed to social media exposure. These results imply that when adolescents engage with social media in a mindful and active manner—particularly on platforms like Instagram—it can positively influence their interpersonal communication development.   Keywords: Social Media Exposure, Interpersonal Communication, Adolescents, Instagram